(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English For the last three decades, critics and discourse on concept or ideology regarding rural economic development is extremely weak. The aim of this paper is to give evidences of systematically failure of the said rural economic development. The basis of the failure is the unclear ideology used as the framework of rural economic development. The "Utopia" as an ideological basis to achieve the economic development goal can not be traced in the practical way in the yield. As a consequences, there is difficulties in assessing the said failure, in addition to substantial negative impact of development activities itself. With the monolithic political infrastructure, the nature of centralistic government as well as growth oriented development will deteriorate natural resources, widening income disparity and rural poverty, widespread of urban informal sector, and instability of feature economic development. To force economic globalization, it is necessary to conduct restructurization of rural economic development. Therefore, the formulating of systematical development activities have to consider the expert on economic sociology, people oriented economic, environment and rural economic development. In the future, the humanistic, fairness, and sustainable economic activity and development should be taken into account. ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Indonesian koreksi kritis dan terbuka terhadap konsep ideologi dalam pembentukan ekonomi pedesaan masih jarang dikemukakan . Tujuan penulisan makalah ini adalah untuk menunjukan adanya gejala kegagalan pembangunan ekonomi pedesaan yang bersifat sistematik. Kegagalan tadi diawali oleh adanya ketidakjelasan ideologi yang dijadikan kerangka kerja pembangunan ekonomi pedesaan . "Utopia" apa yang dijadikan dasar ideologis untuk mencapai keberhasilan pembangunan ekonomi tidak terlacak dengan jelas dalam pragmatisme pembangunan ekonomi di pedesaan. penekanan kegiatan pembangunan ekonomi pedesaan dengan pendekatan pragmatisme di lapangan bukan saja menyulitkan diadakannya pelacakkan terhadap kekeliruan pembangunan ekonomi pedesaan yang bersifat sistematik,melainkan juga membawa dampak negatif yang besar terhadap kegiatan pembangunan itu sendiri. Dengan tatanan politik yang monolitik,pemerintahan sentralistik dan menjebakkan diri dalam tatanan ekonomi yang menekankan pertumbuhan berlebihan bukan saja menimbulkan gejala pengurasan dan penghancuran sumberdaya alam ;melainkanÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â juga memunculkan kesenjangan ekonomi dan pemiskinan yang parah di pedesaan,berkembang pesatnya sektor ekonomi infotmal di perkotaan,serta tingginya kerentaan dan ketidakstabilan perkembangan perekonomian ke depan. Menghadapi tantangan globalisasi ke depan,penataan ulang pembangunan ekonomi pedesaan perlu dilakukan . Oleh sebab itu,perancangan kegiatan pembangunan yang lebih terarah dan sistematik harus melibatkan kalangan ilmuan sosiologi ekonomi,ekonomi kerakyatan ,ekonomi lingkungan dan pembangunan pedesaan. Di masa datang terwujudnya keadilan dalam kegiatan ekonomi yang lebih berkemanusiaan dan berkelanjutan harus mendapat penekanan lebih serius.